The main sequence of quasars: The taming of the extremes. Issue 1 (22nd November 2021) - Marziani, Paola; Bon, Edi; Bon, Natasa; D'Onofrio, Mauro; Punsly, Brian; Śniegowska, Marzena; Czerny, Bożena; Panda, Swayamtrupta; Martnez Aldama, Mary Loli; del Olmo, Ascensión; Deconto‐Machado, Alice; Negrete, C. Alenka; et al.
Abstract: The last few years have seen the confirmation of several trends associated with the quasar main sequence. The idea of a main sequence for quasars is relatively recent, and its full potential for the observational classification and contextualization of quasars' properties has yet to be fully exploited. The main sequence drivers are discussed in terms of the properties of extreme objects. We briefly summarize developments that constrain the viewing angle of the accretion disk in a particular class of quasars (extreme Population B, radiating at low Eddington ratio), as well as inferences on the chemical composition of the broad line emitting gas, and on the nature of radio emission along the quasar main sequence.